The road half traveled: agricultural market reform in Sub-Saharan Africa - Kherallah, Mylene; Delgado, Christopher L.; Gabre-Madhin, Eleni Zaude; Minot, Nicholas; Johnson, Michael E. (EDP Sciences, 2002)
This article reviews the extensive evidence on agricultural market reforms in Sub-Saharan Africa and summarises the impact reforms have had on market performance, agricultural production, use of modem inputs, and poverty. It offers eight recommendations for completing the reform process and developing a new agenda for agricultural markets in Sub-Saharan Africa. The reform experience in Sub-Saharan Africa has varied widely across countries and crop subsectors. The available evidence shows clear progress in some areas and mixed results in others. Most reforms were only partially implemented and policy reversal was common. Once implemented, however, reforms have increased competition and reduced marketing margins, benefiting both producers and consumers. Reforms have also boosted export crop production. On the other hand, food crop production has stagnated and yields have not improved. Further expansion of private trade is constrained by lack of access to credit, uncertainty about the government's commitment to reform, and high transaction costs.